2010
DOI: 10.1101/lm.1746710
|View full text |Cite
|
Sign up to set email alerts
|

Object/context-specific memory deficits associated with loss of hippocampal granule cells after adrenalectomy in rats

Abstract: Chronic adrenalectomy (ADX) causes a gradual and selective loss of granule cells in the dentate gyrus (DG) of the rat. Here, we administered replacement corticosterone to rats beginning 10 wk after ADX. We then tested them in three discrimination tasks based on object novelty, location, or object/context association. Only during testing of the object/context association did ADX rats demonstrate deficits. These findings add to a body of evidence that the hippocampus is necessary when contextual information is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 37 publications
3
51
1
Order By: Relevance
“…The DG, as well as CA3 and CA1, are all capable of performing pattern separation, and there is evidence that this process facilitates context discrimination (Vazdarjanova and Guzowski, 2004; Leutgeb et al, 2007; McHugh et al, 2007; Nakashiba et al, 2012). In a recent study (Spanswick and Sutherland, 2010), rats with a reduction in granule cells in dentate gyrus due to adrenalectomy could discriminate between a novel and familiar object but not an out-of-context and in-context object. As DG-CA3 circuits in particular are important for pattern separation and context discrimination (McHugh et al, 2007; Nakashiba et al, 2012), the deficit in COD in the present study may stem from disruption in pattern separation processes within the hippocampus which are unnecessary for retrieval in the water maze or NOR.…”
Section: Discussionmentioning
confidence: 99%
“…The DG, as well as CA3 and CA1, are all capable of performing pattern separation, and there is evidence that this process facilitates context discrimination (Vazdarjanova and Guzowski, 2004; Leutgeb et al, 2007; McHugh et al, 2007; Nakashiba et al, 2012). In a recent study (Spanswick and Sutherland, 2010), rats with a reduction in granule cells in dentate gyrus due to adrenalectomy could discriminate between a novel and familiar object but not an out-of-context and in-context object. As DG-CA3 circuits in particular are important for pattern separation and context discrimination (McHugh et al, 2007; Nakashiba et al, 2012), the deficit in COD in the present study may stem from disruption in pattern separation processes within the hippocampus which are unnecessary for retrieval in the water maze or NOR.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the current literature suggests that the OiC task relies on function of the hippocampal system in adult rats [12, 30, 34, 36, 38, 39], with a few exceptions [18, 37]. The disparate findings regarding the role of the hippocampus in OiC memory may reflect variable delays employed by different studies which differentially recruit short-term vs. long-term memory processes, or variation in the degree of spatial processing required for discrimination of the contexts during the task.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting possibility is that different subcomponents of the hippocampus are important for different hippocampal-associated memory types. For example, studies have found that adult adrenalectomy results in a selective loss of cells in the dentate gyrus [36,37]. When spatial, recognition, and contextual memory were assessed following adrenalectomy and corticosterone replacement, only contextual memory impairments were found [37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have found that adult adrenalectomy results in a selective loss of cells in the dentate gyrus [36,37]. When spatial, recognition, and contextual memory were assessed following adrenalectomy and corticosterone replacement, only contextual memory impairments were found [37]. Thus, it is possible that in the current study elevated corticosterone levels during gestational stress impacted dentate gyrus development differently than other hippocampal subregions, leading to dissociations in hippocampal-associated memory functions in adulthood.…”
Section: Discussionmentioning
confidence: 99%